Perbedaan Mengunyah Buah Bengkoang dengan Buah Pepaya terhadap Indeks Plak pada Siswa Kelas VII dan VIII Madrasah Tsanawiyah Manbaul Ulum Kabupaten Banjar - Rahmawati, Nur; Rahmawati, Ida; Nuryati, Sri; Astu Rahman, Waljuni (Poltekkes Kemenkes Banjarmasin, 2024)
School age is the right time to improve the ability to maintain dental hygiene. Based on data from the UPT Puskesmas Martapura 2 which had conducted screening related to teeth and mouth at Madrasah Tsanawiyah Manbaul Ulum in September 2022, out of 29 students, 27 students experienced dental caries and 2 students had a Debris Index with an average of 3.0 (high). This study aims to determine the difference between chewing bengkoang fruit and papaya fruit on the Plaque Index in Class VII and VIII students of Madrasah Tsanawiyah Manbaul Ulum, Banjar Regency. This research is an analytic research with a quasi-experimental design and samples were taken by purposive sampling technique with a total sample of 58 respondents. The results showed that the difference in the average (mean) plaque index before and after chewing bengkoang fruit was 2.0765 and the average (mean) plaque index before and after chewing papaya was 1.2358. The results of this study indicate that the difference in the average (mean) bengkoang fruit is greater than papaya fruit. Bengkoang fruit is better at lowering the dental plaque index than papaya fruit. The results of the analysis test using the Independent T-Test obtained the value of ρ<α, so that Ho was rejected and Ha was accepted. In conclusion, there is a difference between chewing bengkoang fruit and papaya fruit on the Plaque Index in class VII and VIII students of Madrasah Tsanawiyah Manbaul Ulum, Banjar Regency. The advice given is that students can keep their teeth and mouth clean and eat foods that are good for their teeth and mouth such as bengkoang fruit or papaya fruit which are proven to reduce plaque found on the tooth surface.